Exosomes and Autophagy: Coordinated Mechanisms for the Maintenance of Cellular Fitness - Baixauli, Francesc; López-Otín, Carlos; Mittelbrunn, Maria (Frontiers in Immunology, 2014)
Conditions resulting from loss of cellular homeostasis; including oxidative stress, inflammation, protein aggregation, endoplasmic reticulum stress, metabolic stress and perturbation of mitochondrial function, are common to many pathological disorders and contribute to aging. Cells face these stress situations by engaging quality control mechanisms aimed to restore cellular homeostasis and preserve cell viability. Among them, the autophagy-lysosome pathway mediates the specific degradation of damaged proteins and organelles, and its proper function is related to cellular protection and increased life span in many model organisms. Besides autophagy, increasing evidence underscores a role for exosomes in the selective secretion of harmful/damaged proteins and RNAs and thus, in the maintenance of cellular fitness. In this perspective article, we discuss the emerging function of exosomes as means of alleviating intracellular stress conditions, and how secretion of harmful or unwanted material in exosomes, in coordination with the autophagy-lysosomal pathway, is essential to preserve intracellular protein and RNA homeostasis. Finally, we provide an overview about the consequences of the spreading of the exosome content in physiological